Effects of canopy cover and pH on polyketide synthase gene transcription in Cladonia stygia and the polyketides produced in natural conditions. - Chhoker, Kamaldeep (2018)
Polyketide synthase (PKS) genes encode large multidomain enzymes that synthesize polyketides (secondary metabolites) but little is known about their biosynthesis. The goals of this study were to identify PKS genes in the Cladonia rangiferina genome in order to target PKS genes in Cladonia stygia, and to compare PKS gene transcription and polyketide production in Cladonia stygia collected from two geologically different locations in Manitoba. The Antibiotic and Secondary Metabolite Analysis Shell (antiSMASH) program identified 41 secondary metabolite gene clusters consisting of 15 Type 1 PKS genes but only two Non-Reducing Type 1 PKS clusters. The significant difference in the concentration of the polyketides, atranorin and fumarprotocetraric acid, between the two locations corresponded with gene expression using the 21 Beta-Ketoacyl Synthase (p=0.040) and 26 Thioesterase domain (p=0.081), suggesting that these PKS domains may play a role in the production of fumarprotocetraric acid and atranorin, respectively, in the C. stygia thallus. October 2018